2020
DOI: 10.1103/physrevmaterials.4.044403
|View full text |Cite
|
Sign up to set email alerts
|

Frustration, ring exchange, and the absence of long-range order inEtMe3Sb[Pd(dmit)2]2: From first principles to many-body theory

Abstract: We parameterize Hubbard and thence spin models for EtMe3Sb[Pd(dmit)2]2 from broken symmetry density functional calculations. This gives a scalene triangular model where the largest net exchange interaction is three times larger than the mean interchain coupling. The chain random phase approximation shows that the difference in the interchain couplings is equivalent to a bipartite interchain coupling, favoring long-range magnetic order. This competes with ring exchange, which favors quantum disorder. Ring excha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 83 publications
2
13
2
Order By: Relevance
“…This 2D picture was reinforced by approximate fits of the 2D triangular Heisenberg model to the magnetic susceptibility data [16,17]. However, more recent ab inito investigations using more sophisticated methods like DFT have suggested that, for most compounds, t B > t S ≈ t r [18][19][20][21][22][23]. Our BS-DFT calculations confirm and strengthen this result as we find that J B J s ≈ J r .…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…This 2D picture was reinforced by approximate fits of the 2D triangular Heisenberg model to the magnetic susceptibility data [16,17]. However, more recent ab inito investigations using more sophisticated methods like DFT have suggested that, for most compounds, t B > t S ≈ t r [18][19][20][21][22][23]. Our BS-DFT calculations confirm and strengthen this result as we find that J B J s ≈ J r .…”
Section: Introductionsupporting
confidence: 81%
“…In molecular crystals such as x-[Pd(dmit) 2 ] 2 , J SE ij is often the largest term [19,22,23]. It arises from virtual hopping processes and usually favors antiferromagnetism [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting spin model could range from a subtly anisotropic quasi-two-dimensional system (for weak charge disproportionation) to quasi-onedimensional spin systems (for large charge disproportionation). However, we note that the geometrical frustration of the magnetic interactions means that this quasi-one-dimensional limit is more stable than one might naively expect [33,35,36]. Therefore, the effective one-dimensionalization of the system when it is dipole ordered could be important for understanding the large "dipole-solid + spin-liquid" phase found by Hotta in her exact diagonalization studies of the NIH model [6].…”
Section: Spin Model In the Dipole Solid Phasementioning
confidence: 78%
“…We note that both V i j and J i j reduce the magnetic ordered moment (see S. 5 in the SM [39]). The mechanism of the reduction can be attributed to the reduction of U and resultant enhancement of the higher-order interactions such as the ring-exchange interactions, which suppress the magnetic long-range orders [47][48][49].…”
mentioning
confidence: 99%